CORPORATE GOVERNANCE PERCEPTION INDEX (CGPI) DAN KINERJA PERUSAHAAN DI INDONESIA; SEBUAH KAJIAN TEORI - Aminullah Aminullah; Mohammad Herli; Hafidhah Hafidhah; Liyanto Liyanto (Fakultas Ekonomi dan Bisnis, 2022)
This article discusses how the Corporate Governance Perception Index (CGPI) may impact how well a business does financially and how the market reacts to news regarding the CGPI. The author arrives to the following conclusion after doing synthesis analysis: it demonstrates that CGPI announcements do, in fact, have an effect on firm performance, growth, and value. The revelation of a company's CGPI rating was another factor that investors considered while making their decisions. Because the CGPI index of the firm reflects the company's capability of being managed by management, the higher the rating achieved indicates the larger the company's capability of being governed